Over in the wetlands : a hurricane-on-the-bayou story - Rose, Caroline Starr (Schwartz & Wade Books, 2015)
Various wetland creatures, from alligators to egrets, enjoy what begins as a calm and peaceful day in the bayou, then prepare for and endure a passing hurricane, and finally settle in for a peaceful night.